Intestinal Protozoan Parasitic Infections in Immunocompromised Child Patients with Diarrhea - Caner, Ayse; Zorbozan, Orcun; Tunalı, Varol; Kantar, Mehmet; Aydoğdu, Sema; Aksoylar, Serap; Gürüz, Yüksel; Turgay, Nevin (Japanese journal of infectious diseases, 2020)
Intestinal protozoan parasites are common causes of infectious diarrhea in children receiving anticancer therapy or undergoing transplantation. Additionally, immunosuppression therapy in such patients may exacerbate the symptoms related to these parasitic infections. The aim of this study was to evaluate the prevalence and diagnostic importance of parasitic protozoan infections in children treated for malignancies or undergoing transplantation, and to highlight the control of intestinal parasitic infections for immunosuppressed patients at a hospital in İzmir, Turkey. In total, 82 stool samples from 62 patients were analyzed by microscopic examination and polymerase chain reaction (PCR) for the presence of coccidian parasites. Our results showed that Cryptosporidium, Cyclospora, and Cystoisospora were present in 22.5% (14/62), 9.6% (6/62), and 3.2% (2/62) of the cases using either method, respectively. The prevalence of these coccidian parasites identified with both methods was 35.4% (20/62). Other intestinal parasites (Blastocystis, Giardia, and Entamoeba coli) were detected in 10 patients. PCR analysis showed the presence of all coccidian parasites in the same stool sample for one patient. Finally, both PCR and microscopic examination of the stools revealed that there is a higher prevalence of Cryptosporidium, Cyclospora, and Cystoisospora in immunocompromised children. These examinations allowed an early start of appropriate antibiotic treatments and led to an increased percentage of correctly treated patients.